Active or Autoclaved Akkermansia muciniphila Relieves TNF-α-Induced Inflammation in Intestinal Epithelial Cells Through Distinct Pathways - Luo, Yuheng; Lan, Cong; Xie, Kunhong; Li, Hua; Devillard, Estelle; He, Jun; Liu, Li; Cai, Jingyi; Tian, Gang; Wu, Aimin; Ren, Zhihua; Chen, Daiwen; et al. (Frontiers in Immunology, 2021)
Intestinal inflammation is a major threat to the health and growth of young animals such as piglets. As a next-generation probiotics, limited studies have shown that Akkermansia muciniphila could alleviate inflammation of intestinal epithelial cells (IECs). In this study, a TNF-α-induced inflammatory model of IPEC-J2 cells, the intestinal porcine enterocytes, was built to evaluate the effects of active or inactive A. muciniphila on the inflammation of IECs. The viability of IPEC-J2 cells was the highest when treated with active (108 copies/mL) or inactive (109 copies/mL) A. muciniphila for 7.5 h (P < 0.01). Whether firstly treated with 20 ng/mL of TNF-α and followed by a treatment of A. muciniphila, or treated with the bacterium firstly and followed by TNF-α treatment, the mRNA level of proinflammatory cytokines (IL-1β, IL-6 and TNF-α) was remarkably reduced (P < 0.05) along with the increased mRNA level of tight junction proteins (ZO-1 and Occludin, P < 0.05). Flow cytometry analysis showed that active or inactive A. muciniphila significantly suppressed the rate of the early and total apoptotic of the inflammatory IPEC-J2 cells (P < 0.05). According to results of transcriptome sequencing, active and inactive A. muciniphila may decline cell apoptosis by down-regulating the expression of key genes in calcium signaling pathway, or up-regulating the expression of key genes in cell cycle signaling pathway. And the bacterium may alleviate the inflammation of IECs by down-regulating the expression of PI3K upstream receptor genes. Our results indicate that A. muciniphila may be a promising NGP targeting intestinal inflammation.